Hydrothermal Carbonization of Biomass: Major Organic Components of the Aqueous Phase. Issue 3 (4th February 2014) - Becker, Roland; Dorgerloh, Ute; Paulke, Ellen; Mumme, Jan; Nehls, Irene
Abstract Process waters obtained from hydrothermal carbonization (HTC) of wheat straw, a biogas digestate derived thereof, and four woody biomass feedstocks were quantified regarding the total organic carbon (TOC) and selected organic compounds. HTC runs revealed that TOC loads were largely unaffected by process severity or type of feedstock whereas the C2–C6 fatty acids, determined by GC, displayed clear effects of temperature and feedstock. HPLC demonstrated simultaneously the initial increase and subsequent consumption of cellulose‐derived furfural and 5‐hydroxymethylfurfural as well as the increase of the lignin‐derived 2‐methoxyphenol. 2‐Methylbenzofuran, an example for a substance potentially harmful to aquatic biota, was observed in high concentration in the HTC liquor from wheat straw‐based feedstocks.